Novel bimetallic MOF phosphors with an imidazolium cation: structure, phonons, high- pressure phase transitions and optical response. Issue 1 (5th December 2018) - Ptak, Maciej; Zarychta, Bartosz; Stefańska, Dagmara; Ciupa, Aneta; Paraguassu, Waldeci
Abstract : We report the synthesis, high-pressure phase transitions and optical properties of novel bimetallic perovskite-type MOFs with imidazolium ions. Abstract : We report the synthesis, crystal structure, phonons and luminescence properties of three novel heterometallic metal organic frameworks (MOFs) with perovskite-like topology of the following formulas: [C3 H5 N2 ]Na0.5 Cr0.5 (HCOO)3 (ImNaCr), [C3 H5 N2 ]Na0.5 Al0.5 (HCOO)3 (ImNaAl) and [C3 H5 N2 ]Na0.5 Al0.475 Cr0.025 (HCOO)3 (ImNaAlCr with 5 mol% of Cr 3+ ). ImNaCr crystallizes in a monoclinic system ( P 2/ n space group) with one imidazolium cation (Im + ) in an asymmetric unit forming six N–H⋯O and four C–H⋯O hydrogen bonds. In contrast to other known heterometallic MOFs, the complete substitution of Cr 3+ ions with smaller Al 3+ ions leads to a change of the crystal symmetry. ImNaAl adopts a monoclinic P 21 / n space group with two distinct Im + cations and different H-bonding patterns. The DSC measurements and XRD single-crystal studies show that the studied crystals do not undergo structural phase transitions in the 80–400 K range. The high-pressure Raman studies of ImNaCr reveal the presence of two reversible structural instabilities, first in the 0.4–1.1 GPa range and second near 4 GPa. The first pressure-induced phase transition involves weak distortion of the metal-formate framework, while the second one is associated with partial and reversible amorphization of the sample. We discuss the stability of heterometallic formate MOFs depending on their building blocks. The luminescence measurements show that both the fully concentrated crystal (ImNaCr) and the diluted one (ImNaAlCr) exhibit a Cr 3+ -based emission characteristic of intermediate ligand field strength. We also show that the spectroscopic properties of heterometallic MOFs depend strongly on the templated cation, i.e. the decreasing size of the organic cation leads to an increase in the crystal field.